Growth rate of sheep fed high fat ration - Lubis, Darwinsyah; Wina, E.M; Rubiono, Bambang E (Indonesian Animal Sciences Society, 1998)
Incorporating high amount of fats into the ration for ruminants will affect the rumen microbes adversely and will reducefiber digestion potential. To correct such negative effects, the free fatty acids used for feed should be bond with Ca++, so it canpassing through the rumen savely (rumen by-pass fat). To test the Ca-fat utilization biologically, 20 growing male Garut shee pwere used and fed with 4 type of isocaloric-isoprotein concentrate feed which were allotted based on a randomized block desig nwith 5 replications. The concentrate (C)-A was a positive control diet, while C-B was substituted with 10% free fatty acids (negative control), C-C was substituted with 10% Ca-fat, and C-D with 15% Ca-fat. The concentrate feed was fed at 500 g/d, while forage (King grass) was 4 kg/d. Results of the experiment showed that the negative effect of free fatty acids can be corrected if it was given in the form of Ca-fat. Growth rate curve indicating a good growing pattern, with average daily gain was 100.18, 87.68, 112.86, and 115.00 g/d (P<0.05) for C-A, C-B, C-C, and C-D treatments, respectively. Total dry matter intake for the respective 4 treatments were 875.9, 855.2, 866.7, and 847.4 g/d (P>0.05). Carcass production was relatively good, where for C-A, C-B, C-C, and C-D were 14.84, 14.68, 16.34, and 15.72 kg (P<0.05) respectively, with final live weights of 34.00, 31.74, 34.58, and 34.30 kg (P<0.05). It can be concluded that Ca-fat (rumen by-pass fat) can be used as an energy source component for growing sheep diet, and give the best result at 10% substitution rate in concentrate feed. Â Key words : Rumen by-pass fat, growth rate, carcass, sheep